Characterization of a nontoxic pyomelanin pigment produced by the yeast Yarrowia lipolytica. (4th November 2019) - Ben Tahar, Imen; Kus‐Liśkiewicz, Małgorzata; Lara, Yannick; Javaux, Emmanuelle; Fickers, Patrick
Abstract: In this study, we report on the ability of the yeast Yarrowia lipolytica W29 to produce an extracellular melanin‐like brown pigment at high yield (0.5 mg/ml) in culture medium supplemented with L‐tyrosine. This pigment has been characterized as pyomelanin and its synthesis was found to occur by the so‐called HGA‐melanin pathway. The purified pyomelanin was found embedded with antioxidant properties as it exhibited a radical scavenging activity toward 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) with IC50 of 230 μg/ml. It was also characterized as noncytotoxic toward two mammalian cell lines, namely the mouse fibroblast NIH3T3 and human keratinocytes HaCaT. When blended with different commercial sunscreens, the purified pyomelanin increased significantly the sun protection factor (SPF) value, highlighting its potential utilization as UV‐filter in cosmetic preparations.